2016
DOI: 10.1111/jhn.12394
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D supplementation and its influence on muscle strength and mobility in community‐dwelling older persons: a systematic review and meta‐analysis

Abstract: BackgroundIt has been suggested that vitamin D status or supplementation is important for maintaining or improving muscle strength and mobility in older adults. The study results, however, do not provide consistent results. We therefore aimed to summarise the available evidence systematically, including only studies conducted in community‐dwelling older persons.MethodsA systematic search of the literature was performed in April of 2016. The systematic review includes studies that used vitamin D with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 74 publications
6
96
1
6
Order By: Relevance
“…In another meta-analysis, vitamin D supplementation to healthy individuals increased upper and lower limb strength (Tomlinson et al, 2015[34]). On the other hand, Rosendahl-Riise et al (2017)[31] did not observe any improvement in muscle strength following vitamin D supplementation (with or without calcium supplements) in community-dwelling older population in their meta-analysis. Epidemiological studies have proposed serum 25(OH)D levels greater than 20 ng/mL as a desirable level for optimal lower extremity strength (Wicherts et al, 2007[37]; Bischoff-Ferrari et al, 2004[8]).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In another meta-analysis, vitamin D supplementation to healthy individuals increased upper and lower limb strength (Tomlinson et al, 2015[34]). On the other hand, Rosendahl-Riise et al (2017)[31] did not observe any improvement in muscle strength following vitamin D supplementation (with or without calcium supplements) in community-dwelling older population in their meta-analysis. Epidemiological studies have proposed serum 25(OH)D levels greater than 20 ng/mL as a desirable level for optimal lower extremity strength (Wicherts et al, 2007[37]; Bischoff-Ferrari et al, 2004[8]).…”
Section: Discussionmentioning
confidence: 89%
“…In a meta-analysis conducted by Rosendahl-Riise et al (2017[31]), vitamin D supplementation alone or its co-administration with calcium supplements significantly improved muscle strength among community-dwelling older individuals. In another meta-analysis, consuming vitamin D by healthy people significantly increased upper and lower limb strength (Tomlinson et al, 2015[34]).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, five different systematic reviews and meta‐analyses have been carried out to determine the effects of vitamin D supplementation on muscle function conducted on different subjects group and using different physical performance measures . One of these more recent investigations, based on the 30 RCTs with no age restriction, concluded that vitamin D supplementation slightly but significantly improved global muscle strength, especially with greater effect in elderly subjects (65 years and older).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of vitamin D on muscle function has been previously reported in systematic reviews and meta‐analyses on all age groups , adults and older adults . However, there is still a lack of consensus regarding the effect of vitamin D supplementation on muscle strength and mobility in postmenopausal women who are at greater risk of vitamin D deficiency and fracture.…”
Section: Introductionmentioning
confidence: 99%
“…More worryingly, the studies in elderly people show no clear benefits on muscle strength or mobility. 17 We have unfortunately created another pseudodisease that is encouraged by vitamin companies, patient groups, food manufacturers, and charities. Healthy people should get vitamin D from small doses of sunshine every day plus dietary sources and trust that millenniums of evolution will have dealt with the fact that in northern climes our vitamin D level naturally drops in winter without us snapping our limbs.…”
Section: Limited Evidencementioning
confidence: 99%